IMPLEMENTING PREPARING DOING CONCLUDING (PDC) LEARNING MODEL TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS - Deviar Nelly (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This research was initiated by the fact that learning activities were about taking notes, memorization, and simple explanations from the teacher without requiring students to analyze a problem and to solve the problems faced in learning. For this reason, the implementation of the Preparing, Doing, and Concluding (PDC) learning model was expected to be a solution to improve students' critical thinking skills. Students were strived to be able to experience an iimprovement in critical thinking skills by preparing, practicing, and concluding based on the activities carried out. This research was conducted at grade IV/A of SDN 003 Sungai Salak. The type of this research was classroom action research. The instrument used was a critical thinking skills test. The results showed that the average score of studets’ critical thinking skills in the first cycle was 66.72 with Sufficient category, and in the second cycle, it increased to 75.52 which was included in Good category. Based on the research results, it was concluded that the implementation of Preparing, Doing, and Concluding (PDC) learning model improved students’ critical thinking skills at grade IV/A of SDN 003 Sungai Salak.